Sphenocratus xinjiangensis Liang, sp. nov., the first authentic record of the dictyopharid subfamily Orgeriinae (Hemiptera: Fulgoroidea: Dictyopharidae) in China - Liang, Ai-Ping; Song, Z.-S.; Jiang, Guo-Mei (Zootaxa, 2006)
A new dictyopharid planthopper species, Sphenocratus xinjiangensis Liang, sp. nov. (subfamily Orgeriinae), is described and illustrated from Xinjiang in northwestern China. This represents the first authentic record of the genus Sphenocratus Horváth, 1910 as well as of the subfamily Orgeriinae in China. The new species extends the range of the genus Sphenocratus and the subfamily Orgeriinae southeastward considerably.